Chemotherapy for advanced poorly differentiated pancreatic neuroendocrine carcinoma. (5th March 2015) - Ikeda, Masafumi; Okuyama, Hiroyuki; Takahashi, Hideaki; Ohno, Izumi; Shimizu, Satoshi; Mitsunaga, Shuichi; Kondo, Shunsuke; Morizane, Chigusa; Ueno, Hideki; Okusaka, Takuji
Abstract Pancreatic neuroendocrine carcinoma (P‐NEC) resembles small cell lung carcinoma in its biologic and clinical features, such as rapid growth and relatively high sensitivity to platinum‐based chemotherapy. And, etoposide plus cisplatin (EP) or irinotecan plus cisplatin (IP), recommended by guidelines for the treatment of small cell lung carcinoma, has also been widely used for the treatment of unresectable NEC. Both regimens have been demonstrated to show favorable efficacy and have been acknowledged as de facto standard regimens for unresectable NEC, although it remains unclear which of the two regimens might yield more favorable outcomes. Therefore, a phase III trial of EP vs. IP has been planned for unresectable gastrointestinal, hepatobiliary or pancreatic NEC by the Japan Clinical Oncology Group. For patients with unresectable NEC who are refractory or intolerant to these regimens, no standard regimens have been established. Everolimus, an mTOR inhibitor, is likely to be effective in such patients, as there have been sporadic reports of the usefulness of everolimus in the treatment of P‐NEC. A multicenter phase II trial is underway to elucidate the efficacy and safety of everolimus in patients with P‐NEC who are refractory or intolerant to EP or IP.